Effect of percentage alumina on the growth kinetics of copper and hardness of Cu-Al2O3 composite - Velasco, Angelito A.; Digsay, Charmaine Florabel A.; Balajediong, Jennifer M.
In this paper, the effect of the amount of alumina reinforcement on the growth kinetics of copper grains during the early stages of sintering and hardness of the composite was investigated. Samples were obtained by mixing the powders of copper and alumina of different compositions (5 percent and 10 percent wt alumina) and compacting at 3,000 psi. Sintering is done using a tube furnace in a nitrogen atmosphere for varying times (10, 20, 40, 80, 160 minutes) and temperatures (750 degree celcius, 850 degree celcius, 950 degree celcius). Afterwards, the samples were prepared for metallographic examination and the average grain size of copper was measured. Photomicrographs showed an increase in copper grain size and decrease in porosity with increasing temperatures. From the kinetic study, the following grain growth equations for 5 percent alumina and 10 percent alumina copper-matrix composite were obtained. Hardness measurements were performed using the Vickers Hardness Tester. Higher hardness of the composite was attained at increased temperatures and percent alumina.
Keywords: Copper; Alumina